Abildgaard, Bibelen og blasfemi - Bach-Nielsen, Carsten (Religionsvidenskabeligt Tidsskrift, 1991)
The Danish neoclassical painter Nicolai Abraham Abildgaard (1743-1809) received his artistic education in rome where he was influenced by the Swedish artist Sergei and the Swiss Fuseli. In 1777, he returned to Copenhagen where he became a professor at the Royal Academy of Fine Arts. In Rome, he encountered the thoughts of the European Enlightenment, revolutionary thoughts and opinions he was to hold for the rest of his life. In Copenhagen, he turned out to be a most satirical critic of the institutions of the absolute monarchy and the state church. Since the Reformation, the Danish clergy has guarded the Lutheran principle of interpretation of the Bible as a field of their own in order to protect the lay reader from misreadings of the text. The enlightened theologians, artists and philosophers show a great effort to let anyone read the Bible just they was he desires. In a number of satirical, blasphemical and erotic drawings with biblical themes in The Royal Collection of Prints and Drawings in Copenhagen, Abildgaard shows how he chose to interpret some passages of the Bible that until then had been explained through reference to other parts of the Bible by the clergy. Abildgaard provokes by reading and showing the Biblical texts without the guidance of the church’s authorized interpretation - as documents of an ancient natural, raw, primitive but absolutely free society. the enlighted freedom of reading the Bible in one’s own manner finds it counterpart in the popular magazines of theological criticism and satire of the 1790s.